Beyond Human Touch: Integrating Soft Robotics with Environmental Interaction for Advanced Applications - Narges Ghobadi; Nariman Sepehri; Witold Kinsner; Tony Szturm (Actuators)
Soft robotics is an emerging field dedicated to the design and development of robots with soft structures. Soft robots offer unique capabilities in terms of flexibility, adaptability, and safety of physical interaction, and therefore provide advanced collaboration between humans and robots. The further incorporation of soft actuators, advanced sensing technologies, user-friendly control interfaces, and safety considerations enhance the interaction experience. Applications in healthcare, specifically in rehabilitation and assistive devices, as well as manufacturing, show how soft robotics has revolutionized human–robot collaboration and improved quality of life. Soft robotics can create new opportunities to enhance human well-being and increase efficiency in human–robot interactions. Nevertheless, challenges persist, and future work must focus on overcoming technological barriers while increasing reliability, refining control methodologies, and enhancing user experience and acceptance. This paper reviews soft robotics and outlines its advantages in scenarios involving human–robot interaction.